Hyperhidrosis of the residual limb: a narrative review of the measurement and treatment of excess perspiration affecting individuals with amputation. Issue 6 (28th December 2021) - Lannan, Ford M.; Powell, Jordan; Kim, Gabriel M.; Hansen, Colby R; Pasquina, Paul F.; Smith, Douglas G.
Abstract : Background: Hyperhidrosis (HH) is a relatively common disorder involving excessive sweating, typically of the palms or axilla. HH can also frequently occur after limb amputation, where the remaining residual limb excessively perspires, leading to an increased risk of dermatological disorders and functional limitations, such as the inability to comfortably or safely wear a prosthesis. Although many treatments have been proposed to treat HH within the dermatology community, they are not widely known by healthcare providers typically involved in caring for individuals with acquired limb loss. Objectives: To appraise the current state of quantitative and qualitative assessment of HH within the residual limb and examine existing and future treatment strategies for this problem. Study design: Narrative Literature Review. Methods: A literature review focused on the assessment and treatment of excessive sweating of residual limbs. Results: There is currently no objective or subjective standard to assess or diagnose HH of the residual limb. Conventional therapies for HH do not always translate to the population of individuals with limb loss. Emerging modalities for treating HH show promise toward a permanent resolution of excess perspiration but require additional studies within people with amputation. Conclusions: Further research is needed to quantify standard values to objectively and subjectively assess and diagnose hyperhidrosis of the residual limb. New and developing treatments for hyperhidrosis require additional studies to assess efficacy and safety in the residual limb.